Coordination Complexes and One-Step Assembly of Lignin for Versatile Nanocapsule Engineering - Bartzoka, Elisavet D; Lange, Heiko; Thiel, Karsten; Crestini, Claudia (ACS sustainable chemistry & engineering, 2016)
Nanoencapsulation of active substances with controlled release in harmless matrices has been the subject of numerous scientific efforts mainly due to the significant biomedical potential of such endeavors. Lignin, the environmentally sustainable byproduct of the pulp and paper industry, contains a multitude of phenolic hydroxyl groups, some of which, are known to readily and strongly chelate with iron ions. In this effort we demonstrated that the concerted use of chelation chemistry, oil in water emulsion principles, and low energy sonication, offers a facile, one-pot strategy to assemble lignin nanocapsules (LNCs) of a controlled architecture. Under these conditions capsules are shown to rapidly assemble utilizing two driving forces, the π-stacking propensity of lignin and its metal chelating ability at alkaline pH. Detailed size exclusion chromatographic evidence validates that the formation of capsules is driven mainly by the enumerated physical interactions with no significant chemical modification of the lignin. The developed process was systematically optimized so as to create the foundations for the morphology and the yield of the capsules being modulated as a function of sonication time, power, and surface contact area. Both pure LNCs and Fe-LNCs were synthesized in high yields with size distributions varying from 0.3 to 6 μm and their release efficiencies were evaluated in detail. As anticipated, the complexation effects of the phenolic OH groups offered to the Fe-LNCs, increased stability, reduced shell thickness (allowing for greater loading efficiencies), and lower release kinetics, compared to LNCs.